2016
DOI: 10.1177/1756285616675777
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of lacosamide as monotherapy and adjunctive therapy in focal epilepsy and its use in status epilepticus: clinical trial evidence and experience

Abstract: Lacosamide (LCM) is approved for anticonvulsive treatment in focal epilepsy and exhibits its function through the slow inactivation of voltage-gated sodium channels (VGSCs). LCM shows comparable efficacy with other antiepileptic drugs (AEDs) licensed in the last decade: in three randomized placebo-controlled trials, significant median seizure reduction rates of 35.2% for 200 mg/day, 36.4-39% for 400 mg/day and 37.8-40% for 600 mg/day were reported. Likewise, 50% responder rates were 38.3-41.1% for 400 mg/day a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 102 publications
1
13
0
Order By: Relevance
“…Serious adverse events were rare and comprised seizures, dizziness, nausea, vomiting, nystagmus, and psychiatric disorders. Adverse events reported in postmarketing studies were similar to those reported in the RCTs . Tolerability seemed lower when LCM was combined with other sodium‐channel blockers, such as carbamazepine, oxcarbazepine, lamotrigine, and phenytoin …”
Section: Safety and Tolerability In Sesupporting
confidence: 69%
See 3 more Smart Citations
“…Serious adverse events were rare and comprised seizures, dizziness, nausea, vomiting, nystagmus, and psychiatric disorders. Adverse events reported in postmarketing studies were similar to those reported in the RCTs . Tolerability seemed lower when LCM was combined with other sodium‐channel blockers, such as carbamazepine, oxcarbazepine, lamotrigine, and phenytoin …”
Section: Safety and Tolerability In Sesupporting
confidence: 69%
“…We examined the reference lists of all identified studies for additional studies. Furthermore, review articles on LCM were available …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…71 For focal-onset seizures, levetiracetam is an ideal choice, but virtually any first-or second-line therapy can be considered, including sodium channel blockers such as lacosamide, oxcarbazepine, and eslicarbazepine. 72,73 Hepatotoxicity caused by AEDs There are more than 900 drugs, toxins, and herbs that are known to be hepatotoxic. 74 A drug's hepatotoxicity may not become apparent until after a large number of patients have taken it, so the risk of hepatotoxicity is usually discovered in the postmarketing phase.…”
Section: Othersmentioning
confidence: 99%